Patents for power : intellectual property law and the diffusion of military technology - Farley, Robert M.; Isaacs, Davida H. (Chicago : The University of Chicago Press, 2021)
In an era when knowledge can travel with astonishing speed, the need for analysis of intellectual property (IP) law - and its focus on patents, trade secrets, trademarks, and issues of copyright - has never been greater. But as Robert M. Farley and Davida H. Isaacs stress in 'Patents for Power', we have long overlooked critical ties between IP law and one area of worldwide concern: military technology. This deft blend of case studies, theoretical analyses, and policy advice reveals the fundamental role of IP law in shaping how states create and transmit defense equipment and weaponry. The book probes two major issues: the effect of IP law on innovation itself and the effect of IP law on the international diffusion, or sharing, of technology.
Previously issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on May 6, 2021).
Keywords: Intellectual property -- United States; Military-industrial complex -- United States; Technology transfer -- United States; Law; Laws of specific jurisdictions & specific areas of law